Expression and structural-functional alterations of α-1-acid glycoprotein at the pathological state - Stekleneva, N.I.; Shevtsova, A.I.; Brazaluk, O.Z.; Kulinich, A.O. (Вiopolymers and Cell, 2010)
The review analyzes up-to-date knowledge on structure and biological functions of α-acid glycoprotein. A special attention is given to alterations in fucosylation, sialylation and branching of orosomucoid at the acute, chronic inflammation and oncotrans formations.